2011
DOI: 10.1111/j.1948-7134.2011.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and control of the sand fly vectors of Leishmania donovani in East Africa, with special emphasis on Phlebotomus orientalis

Abstract: A literature review is provided on the state of knowledge of the ecology and control of the sand fly vectors of Leishmania donovani in East Africa, with a special emphasis on Phlebotomus orientalis. Visceral leishmaniasis caused by L. donovani is a major health problem in several areas in East Africa. Studies conducted in the past 70 years identified P. orientalis Parrot and P. martini Parrot as the principal vectors of L. donovani in Sudan, Ethiopia and Kenya and P. celiae Minter as the secondary vector of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 64 publications
2
111
0
Order By: Relevance
“…This transmission was exacerbated when wastes were disposed in an open space in the environment according to the information from 98.9% of the respondents which was in line with [9] who clearly indicated nocturnal outdoor exposure was also seen in their earlier study in Libo KemKem. In addition, the presence of gorge around houses could be responsible for resting of sandflies being one of the important risk factors for the disease transmission and is in line with [17] who stated sandfly as predominantly outside feeder or in thatch-walled houses that are highly vulnerable to sandfly entry and resting. Seasonal distribution of the disease also revealed that it was common in summer and autumn according to 52.8% of the respondents.…”
Section: Discussionmentioning
confidence: 80%
“…This transmission was exacerbated when wastes were disposed in an open space in the environment according to the information from 98.9% of the respondents which was in line with [9] who clearly indicated nocturnal outdoor exposure was also seen in their earlier study in Libo KemKem. In addition, the presence of gorge around houses could be responsible for resting of sandflies being one of the important risk factors for the disease transmission and is in line with [17] who stated sandfly as predominantly outside feeder or in thatch-walled houses that are highly vulnerable to sandfly entry and resting. Seasonal distribution of the disease also revealed that it was common in summer and autumn according to 52.8% of the respondents.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, both males and females of P. martini and P. celiae are distinguishable using the labrum length, wing length ratio (Gebre-Michael and Lane 1993), and cuticular hydrocarbons (Gebre-Michael and Lane 1994); however, current morphological methods cannot differentiate female P. martini from P. vansomerenae and are referred to as either "synphlebotomus complex" or the "Phlebotomus martini group of species" (Minter 1962, Wijers andMinter 1966). Indeed, this fact leads one to question the veracity of the Þndings of previous studies that no P. vansomerenae females have been found naturally infected with L. donovani (Elnaiem 2011). In the current study we collected 17 Synphlebotomus males (16 P. martini and one P. vansomerenae) and Þve Synphlebotomus females that we collectively called P. martini based on the preponderance of males collected.…”
Section: Discussionmentioning
confidence: 90%
“…The subgenus Synphlebotomus Theodor contains nine described species, of which three (P. martini, P. vansomerenae and P. celiae) are conÞned to the afrotropical region (Lewis 1982) where they are believed to occur sympatrically (Elnaiem 2011). Males of these three species can be differentiated using the shape of the paramere setae and the number of hairs on the coxite tufts (Lewis 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission is mixed anthroponotic and zoonotic although the exact animal reservoir and its contribution have not been identified. There seem to be two different regions: the northern savanna (Sudan, northern Ethiopia) where P. orientalis is the vector with black cotton soil and Acacia-Balanites vegetation and the southern savanna (southern Ethiopia, Kenya) where the vector is P. martini that live around termite mounds 17. There are differences in drug response and post-kala-azar dermal leishmaniasis (PKDL, see below) rates between these two regions.…”
Section: Epidemiologymentioning
confidence: 99%